How to Capture Macro-Financial Spillover Effects in Stress Tests? - Hesse, Heiko (IMF Working Papers; Working Paper ;, 2014)
One of the challenges of financial stability analysis and bank stress testing is how to establish scenarios with meaningful macro-financial linkages, id est, taking into account spillover effects and other forms of contagion. We come up with an approach to simulate the potential impact of spillover effects based on the 'traditional' design of macro-economic stress tests. Specifically, we examine spillover effects observed during the financial crisis and simulate their impact on banks' liquidity and capital positions. The outcome suggests that spillover effects have a highly non-linear impact on bank soundness, both in terms of liquidity and solvency.